Thrombus perviousness is not associated with first-pass revascularization using stent retrievers. Issue 3 (June 2019) - Byun, Jun-Soo; Nicholson, Patrick; Hilditch, Christopher A; Chun On Tsang, Anderson; Mendes Pereira, Vitor; Krings, Timo; Fang, Yibin; Brinjikji, Waleed
Background and purpose: Recent studies suggest that thrombus imaging characteristics such as Hounsfield unit (HU) and perviousness assessed on noncontrast computed tomography (NCCT) and CT angiography (CTA) can predict successful recanalization. We assessed whether these thrombus imaging characteristics could predict successful first-pass recanalization. Methods: We retrospectively reviewed cases of mechanical thrombectomy over a three-year period in which patients received a multiphase CTA and were treated with a stent retriever on first pass. Thrombus attenuation, thrombus enhancement on arterial- and delayed-phase CTA and percentage washout were calculated and their association with first-pass recanalization, successful recanalization and distal embolic complications was studied. Results: Fifty-two mechanical thrombectomy patients were included. First-pass recanalization was achieved in 59.6% and complete revascularization (Thrombolysis in Cerebral Infarction scale 2b/3) was achieved in 84.6%. There was no correlation between first-pass recanalization with thrombus density on NCCT ( p = 0.94), percentage enhancement on arterial ( p = 0.61) and delayed-phase CTA ( p = 0.23) or thrombus length ( p = 0.16). There was no correlation between number of passes and either thrombus density on NCCT ( p = 0.91) or percentage enhancement on arterial- ( p = 0.79) and delayed-phase ( p = 0.14) CTA or thrombus length ( p = 0.34). Clot length was significantly higher in patients with distal embolic complications than in those without (18.5 ± 7.9 vs 11.4 ± 6.6 mm, p = 0.005). Conclusions: Our data suggest that thrombus imaging characteristics on multiphase CTA cannot predict first-pass recanalization or successful revascularization in acute ischemic stroke patients treated with stent retrievers. Longer clot length was associated with higher risk of distal embolic complications.